MinhaHistoriaDigital: An Scalable Fog-Based Architecture for Efficient Vital Signs Monitoring over Smart Cities - Rodrigues, Vinicius Facco; Righi, Rodrigo da Rosa (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2022)
Internet of Things (IoT) is currently present in several areas, including healthcare. IoT offers technology to track and monitor the state of patients remotely. In this context, this article presents MinhaHistoriaDigital, a scalable Fog-based solution for real-time monitoring and data processing from patients wearing wearable devices. Its main contribution is a hierarchical architecture that provides low latency response time.